Following the Fukushima Disaster on (and against) Wikipedia: A Methodological Note about STS Research and Online Platforms. (November 2019) - Moats, David
Science and technology studies is famous for questioning conceptual and material boundaries by following controversies that cut across them. However, it has recently been argued that in research involving online platforms (Wikipedia, Facebook, Twitter, etc.), there are also more practical boundaries to negotiate that are created by the variable availability, visibility, and structuring of data. In this paper, I highlight a potential tension between our inclination toward following controversies and "following the medium" and suggest that sometimes following controversies might involve going "against platforms" as well as with them. I will illustrate this dilemma through an analysis of the controversy over the coverage of the Fukushima disaster on English language Wikipedia, which concerns boundaries between expert and lay knowledge but also the social and technical functioning of Wikipedia itself. For this reason, I show that following the controversy might mean making use of less formatted and less obvious data than Wikipedia normally provides. While this is not an argument against the use of automated digital research tools such as scrapers, I suggest that both quantitative and qualitative researchers need to be more willing to tweak their approaches based on the specificities of the case.